Nanoscale Engineering of P‐Block Metal‐Based Catalysts Toward Industrial‐Scale Electrochemical Reduction of CO2 - Li, Pengfei; Yang, Fangqi; Li, Jing; Zhu, Qiang; Jian Wei Xu; Loh, Xian Jun; Kuo‐Wei Huang; Hu, Wenping; Lu, Jiong (Advanced energy materials, 2023)
The efficient conversion of CO2 to value‐added products represents one of the most attractive solutions to mitigate climate change and tackle the associated environmental issues. In particular, electrochemical CO2 reduction to fuels and chemicals has garnered tremendous interest over the last decades. Among all products from CO2 reduction, formic acid is considered one of the most economically vital CO2 reduction products. P‐block metals (especially Bi, Sn, In, and Pb) have been extensively investigated and recognized as the most efficient catalytic materials for the CO2 electroreduction to formate. Despite remarkable progress, the future implementation of this technology at the industrial‐scale hinges on the ability to solve remaining roadblocks. In this review, the current research status, challenges, and prospects of p‐block metal‐based catalysts primarily for CO2 electroreduction to formate are comprehensively reviewed. The rational design and nanostructure engineering of these p‐block metal catalysts for the optimization of their electrochemical performances are discussed in detail. Subsequently, the recent progress in the development of state‐of‐the‐art operando characterization techniques together with the design of advanced electrochemical cells to uncover the intrinsic catalysis mechanism is discussed. Lastly, a perspective on future directions including tackling critical challenges to realize its early industrial implementation is presented.